Performance analysis of typical airfoils through numerical simulation using fluid-structure interaction - Maia, Igor Albuquerque (2014)
The lift and drag coefficients curves as a function of the angle of attack for typical airfoils were obtained through computer simulation of the fluid-structure interaction. The airfoil was modeled as a section of a 1m chord infinite wing, and the simulation domain was modeled as a wind tunnel with 13m length and 1m width. The finite element used was a 2-D beam element which allows rotation and linear displacement in one axis. The influence of three factors upon the results was studied: the Reynolds number, the finite element crosssection and the material elasticity modulus. Three Reynolds numbers were simulated: Re=106, Re=3x106 and Re=107. Two different cross-sections were used, as well as two material elasticity moduli. The results of the fluid-structure problem were compared with the results of the fluid problem. Therefore, one could evaluate how structure stiffness modifies the pressure field and how this phenomenon influences the lift and drag coefficients.